Turning attraction into repulsion. - Pasquale, E. (Science, 2000)
A series of molecular cues guide axons as they extend in the embryonic environment. In her Perspective, Pasquale discusses new findings that reveal how signals originating from adhesive contacts between axons and the cells they encounter can repel the axon, causing it to break the adhesive contacts and move away (Hattori et al. and Galko and Tessier-Lavigne).